Focus on Gambang - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Mohamad Najib, Mohammad Nor (Penerbit UMP, 2008)
Gambang Science Park had been drawn up for Gambang, an area of 621.51 acres. The component of the park include:...